EFFECT OF AGE AND GENDER ON ARRHYTHMIAS IN PATIENTS WITH CHRONIC HEART FAILURE - Sarwar, Madiha; Imran Majeed, Syed Muhammad; Khan, Muhammad Alamgir; Ahmed, Tausif; Shabbir, Faizania (Pakistan Journal of Physiology, 2013)
Background: Heart failure is a complex clinical syndrome. Modern therapeutics have led to an increase in prevalence and incidence of heart failure among the aging population. The prognosis of heart failure in women has generally been better than in men. The main cause of death in heart failure is supposed to be the sudden arrhythmic death. Arrhythmia frequency varies in both sexes. Different hormonal and electrophysiological differences exist between genders that contribute to arrhythmogenesis. Objective: To determine the effect of age and gender on arrhythmias in patients with chronic heart failure. Methods: This descriptive cross sectional study was conducted at Armed Forces Institute of Cardiology/National Institute of Heart Diseases, from April to August 2013. It involved 48-hour holter monitoring of 53 heart failure patients using holter electrocardiography recorder. Digital ECG data were analysed for type and frequency of arrhythmias. Effect of age and gender on arrhythmias was finally analysed using statistical software. Results: There was no significant association of advancing age with the rise in arrhythmia frequency. Effect of gender on arrhythmias analysis revealed that frequency of arrhythmias was significantly higher in females as compared to males (p-value < 0.05). Conclusion: Arrhythmia frequency was significantly low in men as compared to women, but the effect of age on arrhythmogenesis was not significant. Pak J Physiol 2013;9(2):11–4